We do not part - Han, Kang, 1970-; Yae Won, Emily; Morris, Paige Aniyah (London : Hamish Hamilton, an imprint of Penguin Books, 2025)
"One morning in December, Kyungha receives a message from her friend Inseon saying she has been hospitalized in Seoul and asking that Kyungha join her urgently. The two women have last seen each other over a year before, on Jeju Island, where Inseon lives and where, two days before this reunion, she has injured herself chopping wood. Airlifted to Seoul for an operation, Inseon has had to leave behind her pet bird. Bedridden, she begs Kyungha to take the first plane to Jeju to save the animal. A snowstorm hits the island when Kyungha arrives. She must reach Inseon's house at all costs, but the icy wind and snow squalls slow her down as night begins to fall. She wonders if she will arrive in time to save Inseon's bird-or even survive the terrible cold that envelops her with every step. Lost in a world of snow, she doesn't yet suspect the vertiginous plunge into the darkness which awaits her at her friend's house. There, the long-buried story of Inseon's family surges into light, in dreams and memories passed from mother to daughter, and in the archive painstakingly assembled at the house, documenting a terrible massacre on the island"--
First published.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School
Keywords: Families -- Fiction; Missing persons -- Fiction; Korea -- History -- Chejudo Rebellion, 1948 -- Fiction